SOSIALISASI CARA MENGANALISA KERUSAKAN JALAN PANGERAN RATU JAKABARING PROVINSI SUMATERA SELATAN - Lina Flaviana Tilik; Suhadi; Bastoni; Tri Kurnia Rahayu (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
The rampant damage to roads for urban roads and the lack of service providers in analyzing road damage are things that need to be considered. To overcome this, the role of historians is needed to convey road damage analysis methods according to applicable methods. In this activity, the Sriwijaya State Polytechnic service team together with partner PT. Sembilan Sembilan conducted an analysis of damage to the Pangeran Ratu Road section in Palembang City. From the survey results, it is known that the types of road damage according to the Bina Marga guidelines on the Pangeran Ratu Road section of Palembang consist of pothole damage, asphalt grain weathering, aggregate wear, longitudinal/transverse cracks, subsidence, and crocodile skin cracks. Several alternative road repairs for this type of damage can be in the form of patching aggregates and asphalt to dismantling damaged parts.